Productivity of European beech coppice stands in the Forest Management Area “Donjevrbasko”, Bosnia-Herzegovina - Srđan Keren; Vojislav Dukić; Zoran Govedar; Marijana Kapović-Solomun; Branislav Cvjetković (Glasnik Šumarskog Fakulteta Univerziteta u Banjoj Luci)
The object of this study were three coppice beech stands located in the forest management area “Donjevrbasko” close to Banja Luka in the Republic of Srpska, north-western part of Bosnia and Herzegovina. These coppice stands grow in different conditions. According to available eco-vegetation maps, first beech coppice stand develops in favorable site conditions with high wood production potential for beech. Thereby, we chose such stand which on the first look had fairly good quality of stools. The second coppice stand also grows in good site conditions where high production potential can be expected for beech, but in this case we selected for measurement such stand which has poor technical quality of trees and poor health state. On the contrary, the third coppice stand grows in very poor site conditions where low production potential can be expected for beech. The major goal of the study was to examine the effects of lengthening the rotation periods on wood production, quality and health status of trees in studied coppices.